Ambitious and Anxious: How Chinese College Students Succeed and Struggle in American Higher Education - Hou, Minghui (Journal of International Students, 2021)
In this new publication, Syracuse University Associate Professor Yingyi Ma employs a mixed-method research design to examine and analyze the educational motivations, experiences, and trajectories of a new wave of Chinese undergraduate students from diverse family backgrounds with an emphasis on “the duality of ambition and anxiety” (p. 7). This book challenges the stereotyped expectations of Americans in regards to Chinese students (for instance, that all are from well-off families and have poor English skills). Ma argues that it is pivotal to consider the educational, social, and cultural backgrounds of Chinese internationals in their processes of self-formation in order to have a well-rounded and diverse understanding of Chinese undergraduate students